Challenges Encounter of Information Technology Department in Services Offered at Loadmanna Inc: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Information technology can be defined as a combination of computer andtelecommunications technologies with other technologies such as hardware, software,databases, network technology, and other telecommunications requirements. The purposeof this study was to describe the challenges encountered by the Information TechnologyDepartment in services offered at Loadmanna Inc. Information technology is considered animportant tool for improving healthcare services.However, age, civil status, and sex have a significant effect on the IT department atLoadmanna Inc.; ages were more likely to be capable of gaining more knowledge andanalyzing problems or challenges in terms of services offered, while civil status and sexindicate that the majority of the respondents were single and male. The challengesencountered indicate that the majority was the software, having an average of 3.88 StronglyAgree.To adopt the right technologies, policy makers should have adequate information aboutpresent and future advances. Moreover, the study sought to propose a theory that couldexplain the conceptualization and measurement of service quality. The relationship betweenservice, consumer satisfaction, and purchase intentions. Primary data for this study wascollected from 20 respondents in terms of software, hardware, peopleware, office layout,process, customer service, company income, customer satisfaction, and customerexperience.
Keywords: Business Administration